TEACHING SPEAKING USING COLLABORATIVE APPROACH AT SENIOR HIGH SCHOOL IN WEST BANDUNG - Acep Haryudin; Yana Yana; Efransyah Efransyah (PROJECT (Professional Journal of English Education), 2020)
The objectives of this research are to figure out the significant improvement and achievement of Collaborative Approach in teaching speaking. The method of this research is quantitative method. The population was the tenth grade students of SMAN 2 Padalarang and the sample was consisted of 30 students of tenth grade students. The instruments were pretest-posttest. The data was analyzed using descriptive statistic. The t test data score was 0.000. The score was less than 0.05. So the null-hypothesis was rejected. Therefore, it can be concluded that there was a significant improvement and achievement of Collaborative Approachin teaching speaking. In the other words that collaborative approach can develop the students’ ability of critical thinking, creativity, sincerity, formulating question, self confidence and communication skill. Problem solving and self reflection. The students’ difficulties in speaking is difficult in pronunciation, afraid of making mistakes, mother tongue used, lack of vocabulary and lack of curiosity.